2018
DOI: 10.1016/j.jcot.2017.09.019
|View full text |Cite
|
Sign up to set email alerts
|

A case report on rare occurrence of periosteal ganglion cyst in femoral intercondylar region

Abstract: Ganglions are the cysts derived from myxomatous degeneration of periarticular tissue, commonly found around wrist and foot. Ganglion cysts are uncommon in Knee region and if present their occurrence is mostly incidental and benign. Based on their location, this could be extraarticular or intraarticular. Lesions with similar pathology in subchondral region around joints are lesser common entity called Intraosseous ganglions. Rarer still is the lesion produced by myxomatous degeneration of periosteum of long bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…The recurrence rate for ganglion cysts is generally estimated to be between 15 % and 20 % [ 12 , 13 ]. Prevention for periosteal ganglion cysts include avoiding occupational hazards that has risk of injuring the joint or resting the wrists and fingers after long time of exertion [ 14 ]. This study has been reported in line with the SCARE criteria [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…The recurrence rate for ganglion cysts is generally estimated to be between 15 % and 20 % [ 12 , 13 ]. Prevention for periosteal ganglion cysts include avoiding occupational hazards that has risk of injuring the joint or resting the wrists and fingers after long time of exertion [ 14 ]. This study has been reported in line with the SCARE criteria [ 15 ].…”
Section: Discussionmentioning
confidence: 99%